2021
DOI: 10.1186/s40359-021-00598-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the mental health of US college students

Abstract: Background/aim In the beginning of 2020, the novel Coronavirus disease (COVID-19) caused by the SARS-CoV-2 virus, became a public health emergency in the U.S. and rapidly escalated into a global pandemic. Because the SARS-CoV-2 virus is highly contagious, physical distancing was enforced and indoor public spaces, including schools and educational institutions, were abruptly closed and evacuated to ensure civilian safety. Accordingly, educational institutions rapidly transitioned to remote learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
131
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(147 citation statements)
references
References 22 publications
12
131
1
3
Order By: Relevance
“…Since the beginning of the epidemic, students have had to modify their living and working habits and adapt to remote pedagogical practices. Most universities have been closed, and the loss of jobs or concerns about health may have contributed to the stress and declining mental health of students 25 . Moreover, the duration of the epidemic and the restrictions may also have led to a feeling of weariness and aggravated initial situations of vulnerability linked to the students’ financial situations or social isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the beginning of the epidemic, students have had to modify their living and working habits and adapt to remote pedagogical practices. Most universities have been closed, and the loss of jobs or concerns about health may have contributed to the stress and declining mental health of students 25 . Moreover, the duration of the epidemic and the restrictions may also have led to a feeling of weariness and aggravated initial situations of vulnerability linked to the students’ financial situations or social isolation.…”
Section: Discussionmentioning
confidence: 99%
“…First, by the time of this study, students who were living in China already had stayed in China for nearly one and half years, so they may become homesick which is commonly seen among international students ( 59 , 60 ). In addition, they may worry about the safety of their loved ones in their home countries, which is another feature of university students during the pandemic ( 61 ). Furthermore, the pandemic prevention measures such as lockdown of the university and the required social distancing at the university campus may lead to a sense of social isolation in the students which may finally result in their depression ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…These challenges are expected to be similar, and perhaps even greater among students in professional schools. Negative impacts of COVID-19 on mental health have been reported in both college students [ 16 , 17 ] and health care students [ 18 , 19 ]. However, no studies have specifically reported the mental health impacts of the COVID-19 pandemic among professional eye-care students.…”
Section: Introductionmentioning
confidence: 99%